114 Effects of aquatic conditioning in young horses. II. Bone metabolism. (30th November 2020) - Silvers, Brittany L; Leatherwood, Jessica L; Nielsen, Brian D; Arnold, Carolyn E; Dominguez, Brandon; Glass, Kati; Huseman, Chelsie; Bradbery, Amanda N; Much, Mattea L; Martinez, Rafael E
Abstract: While beneficial in rehabilitation, aquatic exercise effects on bone metabolism in young, healthy horses has not been investigated. Therefore, thirty Quarter Horse yearlings were stratified by age, body weight (BW), and sex and randomly assigned to one of three treatments during a 140-d trial to evaluate aquatic vs. dry exercise on bone metabolism in young horses transitioning to an advanced workload. Treatment groups included non-exercise control (CON; n = 10), dry treadmill exercise (DRY; n = 10), or aquatic treadmill exercise (H2O; n = 10; water: 60% wither height, WH). Animals were housed in individual stalls (3.6 m×3.6 m) from 0600 to 1800, allowed turnout (74 m×70 m) from 1800 to 0600, and fed to meet or exceed requirements. During Phase I, DRY and H2O walked on treadmills 30 min/d, 5 d/wk from d 0–112. Phase II transitioned to an advanced workload 5 d/wk for 28 d (Table 1). Every 14 d, WH, hip height (HH), and BW were recorded. Every 28 d following exercise, serum samples were collected for osteocalcin (OC) and C-telopeptide crosslaps of type I collagen (CTX-1) analysis. Left third metacarpal radiographs on d 0, 112, and 140 were analyzed for radiographic bone aluminum equivalence (RBAE). Data were analyzed using PROC MIXED of SAS. Baseline treatment differences in biomarkers were accounted for using a covariate. There were treatment ′ day interactions (P < 0.01) where OC and CTX-1 remained consistent in both exercise groups while inconsistently increasing in CON. There were no treatment differences (P > 0.30) in RBAE, BW, or HH, but all increased over time (P < 0.01). There was a tendency toward a treatment × day interaction for WH (P = 0.07), characterized by a difference in response by CON during the first 28 d. This study indicates that early forced exercise supports consistent bone metabolism necessary for uniform growth and bone development, while lack of forced exercise results in incongruent bone turnover.